2006
DOI: 10.4103/1463-1741.33538
|View full text |Cite
|
Sign up to set email alerts
|

The risk of noise-induced hearing loss in the Danish workforce

Abstract: The causal association between occupational noise exposure and permanent hearing loss is well-documented and well-founded primary preventive approaches have been developed. However, documentation of the impact on the present prevalence of noise-induced hearing loss in the working population is limited. This study reports on the prevalence of noise-induced hearing loss in a population sample of 788 workers from 11 trades with expected high noise exposure levels and a reference group examined according to the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…While the prevalences in these industries were not low, these industries typically have a very high prevalence of workers with hearing loss 6,31,32 . However, hearing loss can be determined from a single audiogram and will be identifiable on every audiogram after the loss has occurred.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…While the prevalences in these industries were not low, these industries typically have a very high prevalence of workers with hearing loss 6,31,32 . However, hearing loss can be determined from a single audiogram and will be identifiable on every audiogram after the loss has occurred.…”
Section: Discussionmentioning
confidence: 89%
“…These industries have typically been reported as low risk for hearing loss 6,31,33,44 , although a recent study also found higher risks for these industries 21 . Typically ‘low risk’ industries may target audiometric testing for only their most highly exposed workers, and since these exposed workers represent a smaller subset in these industries, the overall hearing loss prevention efforts and culture in these industries may be insufficient.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The High levels of noise can disturb, destroy the ability to hear, and harmful effects and may also put stress of other parts of the body, including the heart. [220]…”
Section: Discussionmentioning
confidence: 99%
“…[1] The most important effect of noise on human is hearing loss (noise induced hearing loss, NIHL), and its nonauditory effects are physical, mental and effects on performance. [23] Some harmful effects of noise on health have been proved and some like hypertension (HTN) and ischemic heart diseases are controversial among researchers. On the one hand, HTN is multifactorial and on the other hand, different races and societies have different levels of resistance against external factors like noise.…”
Section: Introductionmentioning
confidence: 99%